More than two decades of Agri-Environment schemes: Has the profile of participating farms changed?. (15th August 2021) - Cullen, Paula; Hynes, Stephen; Ryan, Mary; O'Donoghue, Cathal
Abstract: The agri-food sector is under increased pressure from consumers to improve on the sustainability of production processes. Policies that incentivise farmers to improve environmental performance, such as agri-environment schemes (AES), are increasingly important. Understanding the choice to participate in these programmes aids policymakers in designing schemes that meet participation and environmental goals. While a number of studies have investigated the decision using cross-sectional data on one or multiple locations, very few have used longitudinal data to investigate the impact of institutional changes over time. Using Ireland as a case study, this paper uses a nationally representative panel of data spanning 23 years to model the impact of scheme and policy changes on the type of farms participating in AES. This paper argues that environmental issues surrounding intensive farms (such as the loss of nutrients and sediment to water and greenhouse gas emissions) are not being optimally addressed in scheme design and further development of such programmes is needed to reduce negative environmental impacts. Highlights: Success of agri-environment schemes at achieving environmental goals has been questioned. Scheme changes towards targeting environmental factors has encouraged extensive farm participation. Low prevalence of intensive farm participants has continued across time. Higher reliance on subsidies means higher participation in agri-environment schemes. Increased opportunity cost for dairy farms due to CAP reform lowers scheme participation.